The Role of BK Teachers in Overcoming Students with Learning Disability in Schools - Yulianti Yulianti; Mona Waroh; Vegestina Rimulawati; Yodia Setiawati (Edumaspul: Jurnal Pendidikan, 2023)
This writing uses the literature study method with research from journals and books published between 1986 and 2023 through electronic databases, namely Google Scholar and Google Book. This article focuses on the important role of Guidance and Counseling Teachers (BK) in helping students overcome learning difficulties which is often referred to as learning disability or learning difficulty which refers to a situation where individuals experience difficulties in learning activities. This article aims to provide useful insights for educators especially counseling teachers on how they can improve the learning achievement of students who face learning difficulties so that these students acquire the knowledge and learning skills needed to succeed in the learning process.